Barriers to promoting breastfeeding in primary health care in Mexico: a qualitative perspective - Hoyos-Loya, Elizabeth; Pérez Navarro, Cecilia; Burrola-Méndez, Soraya; Hernández-Cordero, Sonia; Omaña-Guzmán, Isabel; Sachse Aguilera, Matthias; Ancira-Moreno, Mónica (Frontiers in Nutrition, 2024)
Objective This article aimed to identify the main barriers related to promoting and counseling breastfeeding (BF) at the Primary Health Care (PHC) in Mexico. Methodology A qualitative study with a phenomenological approach was carried out in 88 health centers of the Ministry of Health in the states of Chihuahua, Oaxaca, Chiapas, Veracruz, Mexico, and Yucatan. From September to November 2021, we interviewed 88 key health professionals (HPs) (physicians, nurses, nutritionists, and others) from the PHC and 80 parents of children under 5 years old. In addition, nine focus groups were conducted with parents and caregivers. The data obtained were triangulated with information from focus groups and semi-structured interviews. Results Of the total interviews, 43.2% (n = 38) were nurses, 29.5% (n = 26) were physicians, 19.3% (n = 17) were nutritionists, and the rest were other health professionals. In the group of users, 97.6% (n = 121) were women. We identified contextual barriers, such as the lack of well-trained health professionals and the scarcest nutrition professionals, as material resources in the health units, without mentioning the low user attendance at their control consultations. Furthermore, we identified barriers related to the orientation and promotion of breastfeeding in health units, including a lack of specific strategies, ineffective communication, and the recommendations of commercial milk formulas. Conclusion The results presented reflect the reality of Mexico in relation to BF, making it urgent to take immediate action to improve the quality of nutritional care related to the promotion and orientation of BF at the PHC.